THE WAY TO CREATE A PLANE CREMONA MAP FROM ITS CHARACTERISTIC - Thi Ngoc Giao Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
We describe how to construct a plane Cremona map from its characteristic, which refers to the degree and the list of base-points with their respective multiplicities, and provide some examples of maps of degrees 2 and 3.